2022
DOI: 10.1007/s00405-022-07465-w
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the retrotympanum and its association with mastoid pneumatization in cholesteatoma patients

Abstract: Purpose This study aimed to investigate the variability of the retrotympanum in patients undergoing surgical treatment for cholesteatoma. Methods We included 59 ears of patients undergoing middle ear surgery for cholesteatoma who had preoperative computed tomography scans. A retrospective analysis of the medical records was conducted. The sinus tympani (ST), subtympanic sinus (STS) and facial recess (FR) were classified into types A–C based on the relation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The present study revealed that both the shape of the ST and its interior surface configuration vary considerably amongst human adults. The factors affecting the shape and volume of the ST still remain unclear, however degree of the temporal bone pneumatization is regarded as one of the physiological reasons that can affect the retrotympanum, as well as the ST itself [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that both the shape of the ST and its interior surface configuration vary considerably amongst human adults. The factors affecting the shape and volume of the ST still remain unclear, however degree of the temporal bone pneumatization is regarded as one of the physiological reasons that can affect the retrotympanum, as well as the ST itself [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained due to the fact that retrotympanic pneumatization in cholesteatoma patients is most often a type A configuration and therefore amenable to an endoscopic approach. 29 Thus, in consideration of the overestimated radiologic retrotympanic extension, only meticulous intraoperative evaluation of cholesteatoma extension into retrotympanic subspaces can lead to the decision for a retrofacial approach. In particular, preoperative radiologic disease extension into retrotympanic subsites does not provide reliable information about intraoperative cholesteatoma extension in the retrotympanum.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this potential limitation for transcanal endoscopic approach to the retrotympanum, no conversion to a retrofacial approach for complete cholesteatoma removal was necessary for our cohort. This might be explained due to the fact that retrotympanic pneumatization in cholesteatoma patients is most often a type A configuration and therefore amenable to an endoscopic approach 29 . Thus, in consideration of the overestimated radiologic retrotympanic extension, only meticulous intraoperative evaluation of cholesteatoma extension into retrotympanic subspaces can lead to the decision for a retrofacial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Hool et al found that ST type A may be of higher prevalence in cholesteatoma patients. That is why one has to remember that impaired pneumatization of the mastoid may be associated with a less pneumatized retrotympanum [ 30 ]. As our group of temporal bones was pneumatized, well-aerated only, we wish that the measurements done are to compared with further studies, where diploic and sclerotic mastoids are included.…”
Section: Discussionmentioning
confidence: 99%